TERAPI MINDFULNESS BASED- STRESS BERBASIS VIDEO PADA KESEJAHTERAAN PSIKOLOGIS DAN EFIKASI DIRI IBU DENGAN ANAK SUNTING - Reni Nurhidayah; Katmini Katmini; Yenny Puspitasari (Jurnal Ilmu Keperawatan Jiwa, 2022)
Having a child diagnosed with stunting is one of the stressors for a mother. Feelings of guilt, shock, pressure, and fear of being stigmatized as a failed mother haunt mothers with children diagnosed with stunting. Mothers are required to be able to improve the nutrition of their children as soon as possible without seeing the burden they are feeling. This will disrupt the psychological well-being of mothers with stunting children. The purpose of this study was to determine the effect of mindfulness-based stress reduction video-based therapy on improving the psychological well-being of mothers with stunting children. The research design used was a quasi-experimental one-group pre-test post-test design. Respondents in this study were 15 mothers with children diagnosed with stunting at the Posyandu in Gempolan Village. The intervention was given via video in 3 sessions. Data collection with a questionnaire that is given before and after treatment. Data analysis was carried out using the paired sample T-test. The results showed that the average psychological well-being before intervention was 86 and after the intervention was 128. Self-efficacy before therapy had an average of 35 and after therapy was 53. The results of the paired sample t-test showed p-value = 0.012 for self-efficacy and p-value = 0.021 for psychological well-being. It was concluded that mindfulness-based stress reduction therapy was effective in improving psychological well-being and self-efficacy for mothers with stunting children.